The perception of musical phrasing in correlation to movements in sports routines - Loo, Fung Chiat; Loo, Fung Ying (IDOSI Publications, 2013)
Musical phrasing is an important element in generating expression, demonstrating the direction of music structure, giving a sense of melodic contour and so forth. Like other musical elements such as articulation, dynamics, harmony, meter, rhythm and tempo, musical phrasing also features greatly in the choreography of dance and of sports that involve a routine. As phrasing indicates the start and the end of a unit or sub-unit in a melodic structure, this indirectly correlates to a movement or series of movements in a routine or dance. This study looks into the perception of musical phrasing in movements in a Tai Chi routine from a musical perspective. A competition routine in which choreography and music were evaluated to have the most congruence was chosen. From the video recording, the initiation of musical phrases was recorded and compared with the phrasing of movements in the routine. While many musical elements are congruent with the movements, the result indicates that the Tai Chi practitioner’s perception of musical phrasing as applied to the choreography is rather different from the perception of a musician.